Pelatihan Layanan Makanan, Pengolahan dan Penyajian Minuman Kreasi Bagi Masyarakat Di Desa Manukaya, Kabupaten Gianyar - Pranadewi, Putu Mira Astuti; Juniari, Ni Kadek Eni (Jurnal Pengabdian Kepada Masyarakat Makardhi, 2024)
Manukaya Village, Gianyar Regency was chosen as the location for community service for the TAH Study Program because some people lack skills in the field of food service and processing and serving creative drinks. The local community is often involved in banquets held by the Tampak Siring Presidential Palace so training in the field of food service is very much needed by the local community. In line with the development of Agro Tourism in Manukaya Village, which is mostly oriented towards coffee drink products, training will be carried out on the processing and presentation of KREASI drinks as a reference for alternative products that can be offered. This Community Service is carried out in the form of Food Service Training, Processing and Serving Creative Drinks, with participants as community members who own simple accommodation and agro-tourism in Manukaya village, Pokdarwis members who are involved in the hospitality sector and the Manukaya Village PKK who are often involved in banquet activities at the Tampaksiring Presidential Palace with a total of 30 participants. The output of this activity is: Increasing community skill regarding food and beverage services, creating new beverage creations using natural ingredients produced in Manukaya Village, as well as increasing community capabilities in serving food and drinks. It is hoped that this activity will provide benefits in the form of increasing the knowledge and skills of human resources from Manukaya Village in providing food services and processing and serving creative drinks in the area